2001
DOI: 10.1021/ma001247j
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion Polymerization. 2. Influence of Monomer Partitioning, Termination, and Diffusion Limitations on Polymerization Kinetics

Abstract: We investigate the polymerization kinetics of microemulsions prepared with the cationic surfactant dodecyltrimethylammonium bromide and the hydrophobic monomers n-butyl methacrylate, tert-butyl methacrylate, n-hexyl methacrylate, and styrene. Our previous model for microemulsion polymerization kinetics cannot account for the kinetics of these systems. Using the results of smallangle neutron scattering monomer partitioning studies and an extended kinetic model to analyze the data, the failure of the original ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 31 publications
2
88
2
Order By: Relevance
“…The reaction of a primary free radical with a first monomer is indeed reported in the literature to occur very rapidly, essentially in the diffusion-limited regime. 15 The conversion of MMA was obtained from the weight of PMMA contained in the reaction mixture according to the method already presented in the Experimental Section. Figure 2 presents monomer conversion as a function of reaction time.…”
Section: Kinetics Studymentioning
confidence: 99%
“…The reaction of a primary free radical with a first monomer is indeed reported in the literature to occur very rapidly, essentially in the diffusion-limited regime. 15 The conversion of MMA was obtained from the weight of PMMA contained in the reaction mixture according to the method already presented in the Experimental Section. Figure 2 presents monomer conversion as a function of reaction time.…”
Section: Kinetics Studymentioning
confidence: 99%
“…Deviations of measured microemulsion polymerization kinetics from the Morgan model have been directly related to monomer solubility and the initial microemulsion composition through the introduction of expressions for non-linear monomer partitioning and biradical termination. [15][16][17] A significant development in the modeling of microemulsion polymerization kinetics was the ability to measure monomer partitioning by small angle neutron scattering (SANS). [16] SANS experiments confirmed that when the concentration of monomer does not decrease linearly as a function of conversion, the conversion at which the maximum rate of polymerization occurs moves away from 39%.…”
Section: Feature Articlementioning
confidence: 99%
“…[16] SANS experiments confirmed that when the concentration of monomer does not decrease linearly as a function of conversion, the conversion at which the maximum rate of polymerization occurs moves away from 39%. [15] The transport and partitioning of monomer throughout a microemulsion polymerization introduces complications in the design of block copolymers and in extending the polymer chain length by semi-continuous polymerization. [18,19] Further understanding of semi-continuous microemulsion polymerization is critical in order to reduce the ratio of surfactant to polymer and thereby allow microemulsion polymerization to be commercially feasible.…”
Section: Feature Articlementioning
confidence: 99%
See 2 more Smart Citations